Egypt Economic Monitor, July 2019 : From Floating to Thriving – Taking Egypt's Exports to New Levels - World Bank Group (World Bank, Washington, DC, 2019)
Confronted with pervasive macroeconomic imbalances and microeconomic distortions, the Government of Egypt (GOE) started in 2016 to move forward with important reforms to stabilize the economy and restore confidence. At that time, Egypt was facing daunting economic and structural challenges, unsustainable fiscal and external imbalance and a deterring business environment. The severe foreign currency crunch that peaked in late 2016 motivated the GOE to introduce transformative economic reforms to alleviate the longstanding structural constraints to inclusive growth and macroeconomic stability. The flagship reforms of the economic program were (i) the liberalization of the exchange rate to eliminate the large currency overvaluation and foreign exchange shortages; (ii) a fiscal consolidation program that introduced a ale-added tax (VAT) and a gradual reduction in energy subsidies and the wage bill, and (iii) major energy sector terms to address power outages by public and private investment in generation and establish Egypt's potential as an oil and gas producer by reducing pricing distortions and arrears. These reforms were complemented by efforts to improve the business climate and attract private investment, starting with legislative reforms and the introduction of new laws on industrial licensing, investment, and insolvency. Macroeconomic indicators have reacted positively to the stabilization reforms. Most notable, economic growth has accelerated, the parallel market for foreign currency exchange has been contained, external deficits have narrowed, and international reserves have replenished. Public finances are progressing on a more sustainable path, with a frim containment of spending on price subsidies and a narrowing fiscal deficit. The improvement in macroeconomic conditions have also reflected positively on investors; perceptions, with credit rating agencies upgrading their ratings and outlook for Egypt.